The Phenomenon of Child Problems in Poso Regency - Cristian Tinjabate; Nastainuddin Bolong; Nuraisyah Nuraisyah (Indonesian Journal of Multidisciplinary Science, 2021)
A child is a god's word given to both parents. The child is born in a holy and clean state, the child is born helpless and has not been able to do anything, so it still depends on others who are more mature. The birth of a child in this world is a direct result of the civilization of his parents, this shows that both parents must bear all the risks arising from his actions that are responsible for the maintenance of his child as a mandate of God. Caring for children is a heavy responsibility because we will create a generation that will continue our ideals, as parents that have not been achieved. The purpose of this panel is to understand the Phenomenon of Child Problems in Poso Regency. Metodology of this research qualitatively by prioritizing secondary data for data analysis materials. The results showed that the problem of children in Poso there are four aspects, namely: The results showed that the problem of children in Poso there are four aspects, namely: Civil Rights and Children's Freedom, education, school Participation Figures, Pure Participation figures, rough Participation figures, Family Environment Birth Certificate and Alternative Parenting Early Marriage Primary Health and Welfare Infant Mortality Life Expectancy.